Burkina Faso [In West African agriculture and climate change: A comprehensive analysis] - Somé, Léopold; Jalloh, Abdulai; Zougmoré, Robert B.; Nelson, Gerald C.; Thomas, Timothy S. (International Food Policy Research Institute, 2013)
Burkina Faso is a landlocked country in West Africa covering about 274,000 square kilometers. It is bordered by the Republic of Mali on the north and west; by Cote d’Ivoire on the Southwest; by Ghana, Togo, and Benin on the South; and by Niger on the east. The country has a dry tropi¬cal climate with two contrasting seasons. The rainy season generally lasts from May to October, but its duration decreases progressively from the southwest, amounting to only three months in the northern part of the country. Agriculture accounts for 40 percent of the gross domestic product (GDP) and 60 percent of the total exports of Burkina Faso. Its cropped area is 3.5–4.0 million hectares, representing about 13 percent of the country’s total area and one-third of the arable land. Rainfed agriculture dominates, with largely rudimentary agricultural techniques prevailing among small-scale farmers. Crop production is more diversified in the Sudanian zone (in the southwest), with a variety of roots and tubers (yams, sweet potatoes, and cocoyams), fruits (mangoes, bananas, and citrus fruits), cashews, and sugarcane. The major cash crops are cotton, groundnuts, cowpeas, and sesame.